Satellite Forensics: Analysing Sparse Beacon Data to Reveal the Fate of DTUsat-2 - René W. Fléron (International Journal of Aerospace Engineering)
The CubeSat DTUsat-2 was designed and built by students and faculty at the Technical University of Denmark and launched to low earth orbit on June 2014. Its mission was to aid ornithologists in bird migration research. Shortly after launch and orbit injection, it became apparent that all was not nominal. To understand the problem and find the causes, a forensic investigation was initiated. The investigation used recorded Morse-encoded beacons emitted by the satellite as a starting point. This paper presents the real-life data from DTUsat-2 on orbit and the methodologies used to visualize the key element in the investigation, namely, the correlation between orbit position and the beacon counter. Based on the data presented, an explanation for the observed behaviour of DTUsat-2 is given.